Estudo da fluidodinâmica de um trocador de calor tipo leito fluidizado utilizado no processo de craqueamento catalítico - Pereira, Murilo Lucas (Universidade Federal de São Carlos, 2019)
Petroleum and its derivatives are of prime importance in the development of modern human activities, as evidenced, for instance, by their strong participation in the world energy matrix. However, the non-renewable nature of this raw material makes it imperative to use techniques and processes that maximize the extraction of its useful products, with catalytic cracking being one of them. In this process, heavy hydrocarbon fractions contained in atmospheric residue oil are transformed by means of catalytic reactions in smaller compounds of greater value. One of the key parameters for the good performance of this process is the initial temperature of the catalyst, which is regulated by fluidized bed heat exchangers. That considered, in view of the intimate relationship between the hydrodynamic properties of a packed bed and its heat transfer, this work aimed to study through Computational Fluid Dynamics (CFD) the fluid dynamics of an experimental apparatus developed by YAO et al. (2015a) used to measure the heat transfer coefficient between a fluidized bed and the wall of the exchanger tubes, so that characteristic parameters of the former can be readily provided and thus used in improving the equipment’s operation. To do so, a two-dimensional numerical mesh of the experimental unit was constructed using ICEM-CFD software and the experiment conditions replicated using ANSYS FLUENT v.14.5. By testing different surface gas velocities, it was possible to speculate the presence of an optimum point that would maximize the heat transfer of the equipment, increasing the solids fraction in contact with the exchanger tubes and reducing their residence time (greater solids movement). Finally, the results of the simulation were compared with the predictions of several correlations found in literature, in addition to relevant experimental data, which allowed the evaluation of fluidization characteristics of fine particles, such as their aggregation, forming the so-called clusters. The use of an effective diameter in the drag coefficient equation was proposed in order to represent more accurately these aggregates and a range between 300 and 350 μm was found as the one that fitted better the solids fraction experimental data.
Study of the fluid dynamics of a fluidized bed heat exchanger used in the catalytic cracking process
Keywords: Craqueamento catalítico; Trocador de calor; Fluidodinâmica computacional; Catalytic cracking; Heat exchanger; Computational fluid dynamics; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA